Depressive Symptoms Following Work-Related Violence and Threats and the Modifying Effect of Organizational Justice, Social Support, and Safety Perceptions - Sønderbo Andersen, Lars Peter (Journal of interpersonal violence, 2021)
Work-related threats and violence is a major occupational hazard and the consequences for victims may be a range of physical and psychological symptoms. The purpose of this study was to examine the associations between exposure to work-related violence and threats and subsequent risk for depression and to examine whether the associations were modified by social support, organizational justice and safety perceptions. Questionnaire data was collected in 2010, 2011 and in 2015. A total of 5,342 employees from special schools, psychiatric wards, eldercare and the Prison and Probation Services (PPS) participated in the first round in 2010. The analysis was performed by multivariate logistic regression. Staff exposed for work-related threats and violence had an increased risk for depression compared to non-exposed staff. The risk was highest for staff working in PPS. Compared to low levels, there were a tendency for high levels of social support, organizational justice and safety perception to attenuate the associations between work-related threats and violence and depression. However, none of the differences were statistically significant. Many employees working in human service sectors are exposed to work-related threats and violence which increases the risk for depression. The risk for depression following work-related threats and violence may be modified by social support, organizational justice and the perception of safety workplace. It is recommended that workplaces adopt an integrated organizational approach including both prevention of work-related threats and violence and intervention to modify the health consequences of work-related threats and violence.